Strengthening Vocational High School Leadership through PAKEM SMK: A Project Action Plan–Based Change Project in Riau Province - Muhammad Ihsan Zul; Dadang Syarif Sihabudin Sahid; Winda Damelia; Yoanda Alim Syahbana; Istianah Muslim; Tobi Arfan; Mona Elviyenti; Zainal Arifin Renaldo; Retno Tri Wahyuni; Hamid Azwar; Nabila Aulia Ramadhani (SPEKTA (Jurnal Pengabdian Kepada Masyarakat : Teknologi dan Aplikasi), 2026)
Background: Vocational High Schools (SMKs) play an important role in preparing graduates for employment, higher education, and entrepreneurship. In Riau Province, the role of SMKs has become increasingly strategic due to regional growth in the energy, plantation, and creative industry sectors. Contribution: This study introduces a practice-oriented leadership development approach through the Project Action Plan framework, emphasizing direct implementation of school-based change projects. Method: This study adopted a Participatory Action Research (PAR) approach involving 25 selected SMK leaders from June to September 2022. The program consisted of leadership training, PAP implementation, and project evaluation. Results: The program achieved a high satisfaction level, with 96% of participants reporting being “very satisfied” and all participants recommending the program. Evaluation results showed high scores in project planning (M = 2.57), risk identification (M = 2.52), and PAP document organization (M = 2.70). Conclusion: The PAKEM SMK program demonstrates that combining structured change projects through the PAP framework with continuous mentoring can strengthen leadership capacity and support institutional improvement within SMKs.